Pemberdayaan TPQ Gumukjati dengan Menggunakan Metode ‘Allimna untuk Meningkatkan Baca Al- Qur’an - Wahidah, Nur; Jannah, Nur (Universitas Al-Falah As-Sunniyah Kencong Jember, 2023)
The Al-Quran Education Park is one of the non-formal educational institutions, which has an important role as a means of increasing and expanding religious knowledge, especially in reading the Al-Quran which is the most important thing to be able to understand the meaning, contents and contents of the Al-Quran as a moral, ethical and spiritual foundation. sturdy. The 'Allimna method does not only offer a fast method, it turns out that many of the choices of verses are arguments for the beliefs and practices of Ahlussunnah Waljama'ah, meaning the use of the 'Allimna method in order to achieve better results and the first steps in introducing Hija'iyah letters. and makhrojnya, second is the introduction of harokah, third is the introduction of cursive letters and fourth is the introduction of the science of recitation. The aim of this community service research is to be able to provide an interpretation of the evolution of the use of the 'Allimna method at TPQ Gumukjati, where teachers become more capable and competent in their field. So that problems in using the 'Allimna method can be resolved well, effectively and as efficiently as possible. The method used is EBR (Empowerment Basic Research). The results of this service research are that all problems with learning activities in the classroom using the 'Allimna method have been resolved. Then teachers are more enthusiastic and active in teaching, because there is no longer a burden on the teachers. And the teachers become more enthusiastic and the students also become enthusiastic because with this empowerment all teachers can exchange ideas regarding the good and correct use of the 'Allimna method so that we can solve all problems together. Because one aspect of the success of learning activities using the 'Allimna method is the teacher. So teachers are asked to have sufficient knowledge in teaching and teachers must have knowledge about what will be taught and be competent so that learning objectives can be achieved well.